2017
DOI: 10.1002/chem.201701417
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Growth of Metallo‐supramolecular Polyelectrolytes in Solution

Abstract: Several transition metal ions, like Fe , Co , Ni , and Zn complex to the ditopic ligand 1,4-bis(2,2':6',2''-terpyridin-4'-yl)benzene (L). Due to the high association constant, metal-ion induced self-assembly of Fe , Co , and Ni leads to extended, rigid-rod like metallo-supramolecular coordination polyelectrolytes (MEPEs) even in aqueous solution. Here, we present the kinetics of growth of MEPEs. The species in solutions are analyzed by light scattering, viscometry and cryogenic transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Further developing this technology, Kurth has reported MEPE that demonstrate color to color transition. 35 The kinetics of formation 36 and viscosity 37 of MEPE solutions in different solvents were studied leading to the development of a printing technology. 38 Recently Lahav and van der Boom have demonstrated a novel approach to create multistate electrochromic materials based on two MEPE layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Further developing this technology, Kurth has reported MEPE that demonstrate color to color transition. 35 The kinetics of formation 36 and viscosity 37 of MEPE solutions in different solvents were studied leading to the development of a printing technology. 38 Recently Lahav and van der Boom have demonstrated a novel approach to create multistate electrochromic materials based on two MEPE layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kurth et al reported metallo-supramolecular coordination polymer electrolytes (MEPEs) assembled from transition metal ions (Fe 2+ , Co 2+ , Ni 2+ , and Zn 2+ ) and ditopic ligand 1,4-bis(2,2 ′ :6 ′ ,2 ′′ -terpyridin-4 ′ -yl)benzene (L7) in aqueous solution. 113 Fe-MEPE revealed entangled ber bundles 1.3 ± 0.2 nm wide and hundreds of nm to microns long. MEPE growth kinetics follow a reversible step-growth mechanism.…”
Section: Conductive Coordination Polymer Gelsmentioning
confidence: 95%
“…Assembly of capsules and encapsulation: Further research is taking place on developing novel ways of the polymer shell assembly of capsules . There, metallo-supramolecular complexes can play an important role, and these developments are particularly relevant for enzyme-catalyzed reactions . It is worth noting that in the area of enzyme-catalyzed reactions, traditional layer-by-layer coatings have shown to be very promising. ,, In addition to above-mentioned new methods of LbL assembly, new assembly mechanisms , such as exploring hydrogen bonding would be beneficial.…”
Section: Outlook and Emerging Applicationsmentioning
confidence: 99%